GAMBARANPERENCANAAN MENU MAKANAN DAN POLA KONSUMSI SERTA STATUS GIZI ANAK DI PANTI ASUHAN ACEH SEPAKAT YAYASAN DARUL AITAM KELURAHAN SUKARAMAI KECAMATAN MEDAN AREA TAHUN 2017 - Eva Elisna Tanjung; Jumirah .; Fitri Ardiani (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
Attention to the nutrition and health of childrens in the orphanage isstill relatively minimal,thus allowing high malnutrition rates for foster childrens.Similarly, the comparison of the number of childrensare greater than the number of carers, so the attention to nutritional status will be lower. Another possibility of low funding problems so that the nutritional needs was not comparable with the intake received by orphanage childrens. This study aims to find out the description of Food Planning and Food Consumption Pattern Presented and Nutritional Status of Childrens in Aceh Sepakat Orphanage Darul Aitam Foundation Sukaramai Urban Village Medan Area Year 2017.                The type of this research was observational with cross sectional research design. This research have done by looking at master menu, menu cycle and fund allocation. The data of energy and protein consumption was obtained by using food weighing method, foster child food type using food frequency form and eat frequency seen from how many times of daily meal. The sample in this study amounts to 80 people who are foster childrens in Aceh Sepakat Orphanage. The sampling technique was total sampling. Weight of foster childrens was measured using the scales and height of foster childrens used microtoise. Data were analyzed descriptively.  The results showed that the composition of 100% foster childs food was incomplete, energy consumption 57,5% under category AKG, and consumption of protein 58,8% category under AKG. Nutritional status of foster childrens based on BMI/U there are thin 6,3%, normal 81,3%, grease 7,5% and obesity 5,0%. Based on TB/U there are very short 22,5%, short 38,8% and  normal 38,8%. Orphanages are expected to pay more attention to the arrangement of foods that will be consumed by foster childrens so that foster childrens get the nutrients according to the needs of the body, create a master menu and a fixed menu cycle in order to control the funds available properly and perform weighing periodically 1/6 months. Keywords: Consumption Pattern, Menu Planning, Nutritional Status, Orphanage